Overcoming mental health challenges in higher education: a narrative review - Hyseni Duraku, Zamira; Davis, Holly; Arënliu, Aliriza; Uka, Fitim; Behluli, Vigan (Frontiers in Psychology, 2024)
Background: Mental health among higher education students is a critical public health concern, with numerous studies documenting its impact on student well-being and academic performance. However, comprehensive research on the factors contributing to mental health deterioration, including barriers to seeking psychological help, remains insufficient. Gathering evidence on this topic is crucial to advancing policies, advocacy, and improving mental health services in higher education. Objective: This review explores the unique challenges faced by vulnerable student groups and highlights the factors influencing student well-being and academic engagement, including those exacerbated by the COVID-19 pandemic. The review also addresses barriers to accessing mental health services across various regions and provides evidence-informed recommendations for improving mental health policies and services in higher education, covering both well-researched and underexplored contexts. Methods: This narrative review synthesizes findings from over 50 studies on mental health in higher education. A targeted search was conducted using PubMed, Google Scholar, PsycINFO, CINAHL, and Scopus for studies published between 2013 and 2023. Data were analyzed through a deductive thematic content analysis approach, focusing on key predetermined themes related to student well-being, barriers to mental health services, and recommendations for policy improvements. Results: Several factors influence the mental health of higher education students, with vulnerable groups—including women, minorities, socioeconomically disadvantaged, international, and first-year students—experiencing higher levels of depression, anxiety, and stress. Factors that impact students’ well-being and academic performance include academic pressure, financial stress, lack of social support, isolation, trauma, lack of inclusive practices, and pandemic-related stressors. Institutional barriers, inconsistent well-being measures, data-sharing issues, and regulatory limitations hinder students’ access to mental health services, while stigma and lack of trust in mental health professionals impede care. Conclusion: Improving mental health strategies in higher education requires enhancing mental health services, addressing socioeconomic inequalities, improving digital literacy, standardizing services, involving youth in service design, and strengthening research and collaboration. Future research should prioritize detailed intervention reports, cost analyses, diverse data integration, and standardized indicators to improve research quality and applicability.